2023
DOI: 10.1038/s41467-023-37199-0
|View full text |Cite
|
Sign up to set email alerts
|

Testicular macrophages are recruited during a narrow fetal time window and promote organ-specific developmental functions

Abstract: A growing body of evidence demonstrates that fetal-derived tissue-resident macrophages have developmental functions. It has been proposed that macrophages promote testicular functions, but which macrophage populations are involved is unclear. Previous studies showed that macrophages play critical roles in fetal testis morphogenesis and described two adult testicular macrophage populations, interstitial and peritubular. There has been debate regarding the hematopoietic origins of testicular macrophages and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Sertoli cells were recently shown to be responsible for the colonization of the gonad by monocytes, which subsequently differentiate into macrophages. 85 Since Cyr61 is expressed in the developing Sertoli cells, 22 it would be interesting to determine if low basal activity of YAP/TAZ in Sertoli cells normally contributes to the recruitment of immune cells to the gonad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sertoli cells were recently shown to be responsible for the colonization of the gonad by monocytes, which subsequently differentiate into macrophages. 85 Since Cyr61 is expressed in the developing Sertoli cells, 22 it would be interesting to determine if low basal activity of YAP/TAZ in Sertoli cells normally contributes to the recruitment of immune cells to the gonad.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was previously shown that CYR61 acts a key macrophage chemoattractant in the liver and that its secretion can be induced by YAP/TAZ in hepatocytes, 84 suggesting that the increase in YAP/TAZ activity in Sertoli cell could directly lead to the recruitment of macrophages. Sertoli cells were recently shown to be responsible for the colonization of the gonad by monocytes, which subsequently differentiate into macrophages 85 . Since Cyr61 is expressed in the developing Sertoli cells, 22 it would be interesting to determine if low basal activity of YAP/TAZ in Sertoli cells normally contributes to the recruitment of immune cells to the gonad.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, monocytes that can differentiate into monocyte-derived AM (mo-AM) may play a dominant role ( 23 ). This recruitment of mo-AM alters the population of tissue-resident (TR) AM ( 24 , 25 ) and represents an important mechanism for the phenotypic and functional adaptation of AM during infection. Our study does not distinguish between different subpopulations of AM.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous fate mapping studies of the origins and turnover of tissue-resident macrophages in various organs of the mouse, including studies of pancreas, thymus, testis, tongue and adrenal [27][28][29][30][31] since a previous review [2]. They include an analysis of skeletal muscle [32].…”
Section: The Interpretation Of Fate-mapping Studies In Micementioning
confidence: 99%
“…Diversity in turnover kinetics has also been described for sub-populations of macrophages defined by surface markers within individual tissues (e.g. [27,28,31]).…”
Section: The Interpretation Of Fate-mapping Studies In Micementioning
confidence: 99%